Cranial morphology of Bachia bicolor (squamata: Gymnophthalmidae) and its postnatal development - Tarazona, Oscar A. (2008)
This study describes the adult cranial osteology of the gymnophthalmid lizard Bachia bicolor, and its variation during postnatal development. Descriptions are based on a size series of osteological preparations, including dry skeletons and cleared and double-stained specimens. The adult skull morphology of B. bicolor is similar to that of other gymnophthalmids; however, it shows some particular characters that are convergent with those of several serpentiform lizards. The skull design of B. bicolor has two remarkable structural modifications: (1) the presence of the basisphenoid rostral process by the ossification of the cartilage trabecula communis during postnatal development, and (2) the broad orbitosphenoid bone. The latter is a compound bone (chondral and membranous) that forms part of the anterior braincase floor. Some of the cranial modifications observed in B. bicolor arise during postnatal development, suggesting an important role for possible heterochronic changes.